PENERAPAN METODE SMART PADA SISTEM PENUNJANG KEPUTUSAN PADA CU LANTANG TIPO SANGGAU - Riyadi Iskandar; Alfred Putra; Hedianto Hedianto (LPPM Universitas Widya Dharma Pontianak, 2021)
Credit cooperatives or credit unions have a very large role in the welfare of the community, development and helping the growth of the Indonesian economy. One of them is by doing credit loan services provided by cooperatives to its members. Lantang Tipo Credit Cooperative Sanggau Branch Office is one of the credit cooperatives which is engaged in savings and loan services and services for members who wish to apply for loans. In lending this still uses manual calculations in lending decisions, therefore a decision support system is needed that can help in handling a decision to choose a better decision. One problem that can be resolved with the decision support system is the provision of credit loans using the Simple Multi Attribute Rating Technique (SMART) method. The results of the calculation of this decision support system are based on the criteria set by the Lantang Tipo Credit Union Cooperative, Sanggau Branch Office to provide a decision on the feasibility of loan lending and present a report on the decision on loan lending to members who apply for loan loans.The conclusion obtained from the analysis is that this decision support application can help the Lantang Tipo Credit Cooperative of the Sanggau Branch Office in giving decisions on the acceptance or rejection of loan loans to members Keywords: Support, Systems, Decision, Credit, Lending